2016
DOI: 10.1124/jpet.116.238444
|View full text |Cite
|
Sign up to set email alerts
|

Allylpyrocatechol Attenuates Collagen-Induced Arthritis via Attenuation of Oxidative Stress Secondary to Modulation of the MAPK, JAK/STAT, and Nrf2/HO-1 Pathways

Abstract: Rheumatoid arthritis (RA), an inflammatory autoimmune disorder, is characterized by synovial hyperplasia and bony destruction. The pathogenesis of RA includes redox dysregulation, concomitant with increased levels of proinflammatory mediators. As the ability of allylpyrocatechol (APC), a phytoconstituent of Piper betle leaves, to alleviate oxidative stress has been demonstrated in patients with RA, its antiarthritic activity was evaluated in an animal model of arthritis, and the underlying mechanism(s) of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that MAPK p38/Nrf2 signaling pathway plays an important role in response to oxidative stress. [15][16][17] The expression levels of p-p38 and p38 were detected by western blot. As shown in Fig.…”
Section: Mapk P38/nrf2/ho-1 Signaling Pathway Was Implicated In the Ementioning
confidence: 99%
“…It has been demonstrated that MAPK p38/Nrf2 signaling pathway plays an important role in response to oxidative stress. [15][16][17] The expression levels of p-p38 and p38 were detected by western blot. As shown in Fig.…”
Section: Mapk P38/nrf2/ho-1 Signaling Pathway Was Implicated In the Ementioning
confidence: 99%
“…ROS, such as superoxides, hydrogen peroxide, and hydroxyl free radicals, are constantly produced in aerobic organisms. Elevated levels of ROS and free radical oxidative damage boost the generation of proinflammatory conditions and cause disease progression [ 10 , 33 ]. For this reason, we next investigated the potential antioxidant activities of NO-Fr, NS-Fr, and RA-Fr by measuring DPPH free radical scavenging activity.…”
Section: Resultsmentioning
confidence: 99%
“…Another key component of inflammation is oxidative stress, which reflects an imbalance in ROS, which reduces the production of antioxidant enzymes that protect tissues from oxidative damage [ 7 , 8 ]. In particular, the induction of phase 2 detoxifying enzymes and cytoprotective genes, such as heme oxygenase-1 (HO-1), glutamate-cysteine ligase catalytic (GCLC), and NAD(P)H quinone oxidoreductase 1 (NQO1), is mediated by nuclear factor erythroid-2-related factor 2 (Nrf2), which plays a central role in protecting cells from inflammatory and oxidative damage [ 9 , 10 , 11 ]. Therefore, developing anti-inflammatory agents and antioxidants that can control the activation of macrophages for preventing and treating various diseases is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Protein tyrosine kinase/signal transducer and activator of transcription (JAK/STAT) is a signaling transduction pathway that is closely associated with inflammation ( 9 ), oxidative stress ( 10 ), cell injury and apoptosis ( 11 ). Janus activated kinase signal transducer 2 and activator of transcription 3 (JAK2/STAT3) is an important signal transduction pathway in the JAK/STAT family.…”
Section: Introductionmentioning
confidence: 99%